PENGARUH DISIPLIN DAN KEPUASAN KERJA TERHADAP MOTIVASI KERJA DAN DAMPAKNYA TERHADAP KINERJA PEGAWAI DI KANTOR PELAYANAN PAJAK PRATAMA MEDAN PETISAH - Dedi Kurnia (Universitas Islam Islam Sumatera Utara, 2020)
The formulation of the problem in this research is how the influence of dicipline on work motivation. Influence of job satisfaction on work motivation. Influence of dicipline on performance. Influence of job satisfaction on performance. Influence of work motivation on performance.The purpose of this research is for know influence and analize of dicipline on work motivation. For know influence and analize of job satisfaction on work motivation. For know influence and analize of dicipline on performance. For know influence and analize of job satisfaction on performance. For know influence and analize of work motivation on performance. The sample in this research is 88 employees, with data analysis technique used is multiple linear regression analyze. The results of this research explain that dicipline effect has a positive and significant on work motivation. Job satisfaction effect has a positive and significant on work motivation. Dicipline effect has a positive and significant on performance. Job satisfaction effect has a positive and significant on performance. Work motivation effect has a positive and significant on performance